High performance of PES-GNs MMMs for gas separation and selectivity - Alaa Mohamed (Elsevier, 2022)
In this study, graphene nanosheets (GNs) were incorporated into polyethersulfone (PES) by phase inversion approach for preparing PES-GNs mixed matrix membranes (MMMs). To investigate the impact of filler content on membrane surface morphology, thermal stability, chemical composition, porosity and mechanical properties, MMMs were constructed with various GNs loadings (0.01, 0.02, 0.03, and 0.04 wt%). ​The performance of prepared MMMs was tested for separation and selectivity of CO2, N2, H2 and CH4 gases at various pressures from 1 to 6 bar and temperature varying from 20 to 60 °C. It was observed that, compared to the pristine PES membrane, the prepared MMMs significantly improved the gas separation and selectivity performance with adequate mechanical stability. The permeability of CO2, N2, H2 and CH4 for the PES + 0.04 wt% GNs increases from 9 to 2246, 11 to 2235, 9 to 7151, and 3 to 4176 Barrer respectively, as compared with pure PES membrane at 1 bar and 20 °C due to improving the membrane absorption and porosity. In addition, by increasing the pressure, the permeability and selectivity of CO2, N2, H2 and CH4 are increased due to the increased driving force for the transport of gas via membranes. Furthermore, the permeability of CO2, N2, H2 and CH4 increased by increasing the temperature from 20 to 60 °C due to the plasticization in the membranes and the improvement in polymer chain movement. This result proved that the prepared membranes can be used for gas separation applications.